Morphological interference in the process of mastering English speech in conditions of interaction of Tuvan, Russian and English as a foreign language - Baykalova, Elena D.; Artyna, Mira K.; Dorzhu, Namdolmaa S.; Ochur, Taigana K.; Mongush, Dolaana S. (Opción, 2019)
Multilingualism in the era of globalization is becoming more persistent and objective need, which has created an imperative to study the problem of education and raising the younger generation so that they thrive under conditions of multiculturalism. This work is devoted to the study of morphological interference in the process of mastering English speech under conditions of interaction between Tuvan, Russian and English as a foreign language in multilingual students. The results of this study should be widely applicable to the practice of teaching English in developing a set of exercises to overcome this type of interference.